2023
DOI: 10.1002/ente.202300228
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Carbon‐Based Materials for Improving the Performance and Stability of Perovskite Solar Cells

Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) attract many researchers in the field of photovoltaic because of their high‐power conversion efficiency and low‐cost manufacturing. However, improper interfacial charge transfer, perovskite degradation, and poor stability are major concerns for their commercialization and scale‐up. Significant efforts have been made in recent years mainly by employing different strategies such as optimizing fabrication, developing novel materials, use of additives, and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 256 publications
0
1
0
Order By: Relevance
“…The use of hydrophobic HTM or carbon-based electrodes help in improving the device longevity; however, these materials have suppressed the efficiency of the PSCs. 161–164 Following the initial exploration of carbon based perovskite solar cells introduced by Chang et al in 2016, 165 a range of strategies has been suggested to enhance device performance and reaching to 15.35% PCE. 166 These strategies encompass optimizing fabrication techniques, engineering solvents, adjusting compositions, refining interfaces, optimizing charge transport layers, and more.…”
Section: Strategies To Enhance Perovskite Solar Cells’ Stability Agai...mentioning
confidence: 99%
“…The use of hydrophobic HTM or carbon-based electrodes help in improving the device longevity; however, these materials have suppressed the efficiency of the PSCs. 161–164 Following the initial exploration of carbon based perovskite solar cells introduced by Chang et al in 2016, 165 a range of strategies has been suggested to enhance device performance and reaching to 15.35% PCE. 166 These strategies encompass optimizing fabrication techniques, engineering solvents, adjusting compositions, refining interfaces, optimizing charge transport layers, and more.…”
Section: Strategies To Enhance Perovskite Solar Cells’ Stability Agai...mentioning
confidence: 99%